Isolation of a jadomycin incorporating l-ornithine, analysis of antimicrobial activity and jadomycin reactive oxygen species (ROS) generation in MDA-MB-231 breast cancer cells. (August 2018) - Forget, Stephanie; Robertson, Andrew W.; Hall, Steven; MacLeod, Jeanna; Overy, David; Kerr, Russell; Goralski, Kerry; Jakeman, David
Abstract Herein, we report the characterization and antimicrobial activity of a previously unreported jadomycin (1 ) obtained from a culture ofS. venezuelae ISP5230 withl -ornithine (Orn).1 arises from the rearrangement of a putative five-membered ring containing jadomycin incorporating Orn, whereby intramolecular attack of the E-ring carbonyl from theδ -NH2 group of the Orn side chain results in collapse of the oxazolone ring and formation of a stable six-membered lactam. This rearrangement produces a jadomycin with a 3a hemiaminal position that is susceptible to solvolysis. A structure–activity relationship is discussed based on the antimicrobial activity of1 compared to previously reported jadomycins, providing evidence that the presence of a 3a hemiaminal enhances activity against Gram-positive bacteria. Additionally, assays to quantify reactive oxygen species (ROS) generation and cell viability were performed using a series of nine jadomycins. Compound1 was found to produce the highest ROS activity and to possess the greatest cytotoxicity against MDA-MB-231 breast cancer cells.